Importance of Teaching Ergonomics in Dental School Education - Botta-Maltese, Ana Carolina; Wajngarten, Danielle [UNESP]; da Costa Neves, Tamíris [UNESP]; Pazos, Júlia Margato [UNESP]; Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (Sciencedomain International, 2023)
Aims: The aim of this study was to present the prevalence of musculoskeletal symptoms in dental students and their ergonomics knowledge, the challenges of the implementation of ergonomics in dental school curriculum, and the teaching of ergonomics in dental courses. Methodology: This manuscript was supported by scientific evidence found in the literature obtained from Science Direct, Scientific Electronic Library Online (SCIELO), and National Library of Medicine (MEDLINE) databases, as well as the authors’ experience in ergonomics education and research studies. Results: Most dental students have reported pain in their neck, lower back, and shoulders. Although students have experienced musculoskeletal symptoms, they have a limited perception of work risk factors due to the lack of ergonomics education while in dental school. The challenges of its incorporation could be addressed through curricular revisions. Conclusion: Implementation of ergonomics in the dental curriculum at the beginning of preclinical training and its reinforcement later in clinical practice can prevent musculoskeletal disorders in dental students. Curricular revision needs to be accompanied by epidemiologic studies, faculty development, and timely evaluation in order to customize ergonomics educational programs in dental curriculum and identify areas of success as well as those needing improvement.